Process optimization in simultaneous saccharification and fermentation system for bioethanol production from Pakchong grass (Pennisetum purpureum cv Thailand) - Ningrum, Annisa Septyana; Sihombing, Erick Rafael; Murdiyanto, Satria Ahmadsyah; Wahyuono, Ruri Agung (International Journal of Renewable Energy Development, 2026)
To support the 2060 Net Zero Emission (NZE) target under the Paris Agreement, increasing the proportion of bioethanol blends to 20-30% has become a national priority. However, limited sugarcane-derived bioethanol production in Indonesia highlights the urgent need for alternative biomass sources. Pennisetum purpureum cv. Thailand (Pakchong grass) presents a promising candidate due to its high biomass yield, low lignin content, and adaptability. This study aims to optimize the bioethanol production process from Pakchong grass through pretreatment, enzymatic saccharification, and fermentation, utilizing a modified simultaneous saccharification and fermentation (SSF) scheme. Pretreatment optimization using NaOH (1-5%) revealed that 5% NaOH for 15 minutes effectively removed up to 70% lignin and 78% hemicellulose while retaining 66% cellulose. Enzymatic saccharification using 10 g/L cellulase for 5 days yielded 76.18% glucose conversion without requiring costly additives. Bioethanol fermentation was conducted using six fermentation schemes involving simultaneous (SSF), fed-batch (FSSF), and pre-saccharification strategies (PSFF). Among them, the two-feed FSSF (SE2) produced the highest ethanol yield (32 g/L, 95.41% efficiency), outperforming both conventional SSF (SE1) and PSFF variants. The findings emphasize the importance of synchronizing enzymatic hydrolysis with yeast metabolic activity. This work demonstrates the feasibility of integrated pretreatment and fermentation strategies for bioethanol production from Pakchong grass, offering insights for scalable and cost-effective renewable fuel development in tropical regions.